Enhanced Functional Connectivity between the Bilateral Primary Motor Cortices after Acupuncture at Yanglingquan (GB34) in Right-Hemispheric Subcortical Stroke Patients: A Resting-State fMRI Study - Ning, Yanzhe; Li, Kuangshi; Fu, Caihong; Ren, Yi; Zhang, Yong; Liu, Hongwei; Cui, Fangyuan; Zou, Yihuai (Frontiers in Human Neuroscience, 2017)
Increasing neuroimaging researches in stroke rehabilitation had revealed the neural mechanisms of rehabilitation therapy. However, little was known about the neural mechanisms of acupuncture therapy in subcortical stroke patients. The aim of this study was to investigate the changes of functional connectivity (FC) between the bilateral primary motor cortices (M1s) after acupuncture intervention in right subcortical stroke patients. Twenty right-hemispheric subcortical stroke patients and twenty healthy subjects were recruited to undergo one functional magnetic resonance imaging (fMRI) scanning. The scanning consisted of resting-state fMRI before and after needling at Yanglinquan (GB34), and task-evoked fMRI. The most significant active point during the left passive thumb-to-index task was chosen as the seed point. The seed-based FC analysis of the bilateral M1s was performed. Stroke patients revealed decreased FC between the bilateral M1s compared with healthy subjects, and the decreased FC was significantly enhanced after acupuncture at GB34. Acupuncture could increase the intrinsically decreased FC between the bilateral M1s which provided further insight into the neural mechanisms of acupuncture for motor function recovery in stroke patients.